DEVELOPMENT OF COMPETENCIES AND COMPETENCIES OF TEACHERS IN MODERN CONDITIONS - Kusainov G. M., Mnaidarova S. S. (Development of Modern Competencies of Teachers and Students through the Study and Popularization of the Traditional Culture of the Peoples of the Russian Federation, 2021)
The article discusses the concepts of “competence” and “competence” of a teacher, their distinctive characteristics, reveals effective ways of forming pedagogical competencies and competence in the process of using collective training sessions.
Keywords: педагог; компетентность; компетенция; competence; teacher; pedagogy; педагогизация; коллективные учебные занятия; collective training sessions